Analisis Kualitas Air di Sungai Marbau - Nur Hasanah Pohan; Arman Harahap (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to analyze the quality of river water and the water quality status of the Marbau watershed in North Labuhanbatu Regency based on water quality criteria and to formulate a pollution control strategy that needs to be implemented. The method used is a quantitative descriptive method by analyzing the status of river water quality based on the pollution index. The results showed that the P1 value of Marbau river water ranged from 0.94 to 1.82. The recommended pollution control strategies are: 1) maintaining river protection zones involving environmental cadres and green communities in monitoring; 2) monitoring and controlling water pollution along the river; 3) improve river water quality monitoring; 5) supervision of the discharge of waste water into rivers; 4) granting permits for disposal of wastewater (IPLC) into rivers must pay attention to the condition of the capacity to accommodate river pollution loads and enforce environmental law against business actors who violate established environmental quality standards. In conclusion, the quality of the Marbau river has decreased with the water quality status being slightly polluted. The recommendations for water pollution control strategies that need to be implemented are progressive strategies. Keywords: Water Quality, North Labuhanbatu, Marbau